ENTREPRENEURSHIP ORIENTATION OF STUDENTS ON THE BASIS OF AN INTEGRATIVE APPROACH AS A KEY FACTOR IN THE DEVELOPMENT OF COMPETENCIES (American Journal of Interdisciplinary Research and Development, 2024)
This scientific article explores the role of entrepreneurship as a key factor in the development of competencies among students. Recognizing the importance of a holistic approach to education, this article emphasizes the integration of entrepreneurship education within academic curricula to foster the acquisition of diverse competencies. By examining the relationship between entrepreneurship and the development of cognitive, interpersonal, and practical skills, this study highlights the benefits of an integrative approach in preparing students for future challenges and enhancing their employability. The article concludes with recommendations for educators and policymakers on incorporating entrepreneurship education into various educational settings.